How Should We Teach Nature Protection? Self-Determination and Environmental Attitudes - Tessa-Marie Baierl; Franz X. Bogner (MDPI AG, 2023)
Environmental attitudes are supportive for learning about the environment and for pro-environmental engagement. The question, then, is how to strengthen and establish environmental attitudes. Based on a sample of 429 middle and high school students, we investigated the effect of self-determination-based motivation on environmental attitude. While high levels of self-determination (i.e., intrinsic motivation) positively affected pro-environmental attitude (β = 0.40), low levels of self-determination (i.e., external regulation) negatively affected attitude (β = -0.31). Our data further pointed to a distinct trajectory of self-determination and inclusion of nature throughout adolescence (high scores for 12-year-olds that decline to a minimum around 15-16-years old); a trend that has already been shown for environmental attitude. Such a dip might help derive teaching recommendations in environmental education, e.g., by supporting high scores in time to attenuate a decline. Further teaching recommendations include strengthening students' self-determination through their basic needs (autonomy, competence, and relatedness).